MCU Up‐regulation contributes to myocardial ischemia‐reperfusion Injury through calpain/OPA‐1–mediated mitochondrial fusion/mitophagy Inhibition. Issue 11 (9th September 2019) - Guan, Lichun; Che, Zhimei; Meng, Xiangdong; Yu, Yong; Li, Minghui; Yu, Ziqin; Shi, Hui; Yang, Dicheng; Yu, Min
Abstract: Mitochondrial dynamic disorder is involved in myocardial ischemia/reperfusion (I/R) injury. To explore the effect of mitochondrial calcium uniporter (MCU) on mitochondrial dynamic imbalance under I/R and its related signal pathways, a mouse myocardial I/R model and hypoxia/reoxygenation model of mouse cardiomyocytes were established. The expression of MCU during I/R increased and related to myocardial injury, enhancement of mitochondrial fission, inhibition of mitochondrial fusion and mitophagy. Suppressing MCU functions by Ru360 during I/R could reduce myocardial infarction area and cardiomyocyte apoptosis, alleviate mitochondrial fission and restore mitochondrial fusion and mitophagy. However, spermine administration, which could enhance MCU function, deteriorated the above‐mentioned myocardial cell injury and mitochondrial dynamic imbalanced. In addition, up‐regulation of MCU promoted the expression and activation of calpain‐1/2 and down‐regulated the expression of Optic atrophy type 1 (OPA1). Meantime, in transgenic mice (overexpression calpastatin, the endogenous inhibitor of calpain) I/R model and OPA1 knock‐down cultured cell. In I/R models of transgenic mice over‐expressing calpastatin, which is the endogenous inhibitor of calpain, and in H/R models with siOPA1 transfection, inhibition of calpains could enhance mitochondrial fusion and mitophagy, and inhibit excessive mitochondrion fission and apoptosis through OPA1. Therefore, we conclude that during I/R, MCU up‐regulation induces calpain activation, which down‐regulates OPA1, consequently leading to mitochondrial dynamic imbalance.